The Effect of Digital Technology on Traditional Game Culture Preservation, Behavior Change, and Community Participation - Anggara, Diego Wisnu; Purnomo, Adelaide Gracegefa (Brawijaya University Library, 2025)
The rapid advancement of digital technology has significantly influenced the preservation and transformation of traditional games, impacting player behavior and community participation. As digital platforms increasingly replace traditional play environments, concerns arise about the potential decline of cultural heritage while presenting new revitalization opportunities. This study examines digital technology's role in documenting and preserving traditional games, its influence on behavioral changes, and its implications for community engagement. Employing a quantitative research approach, data were collected through a structured online survey involving 500 respondents and analyzed using SmartPLS (PLS-SEM) to determine the relationships among variables. The findings indicate that digital technology positively affects traditional game preservation (β = 0.650, p = 0.000), behavioral changes (β = 0.773, p = 0.000), and community participation (β = 0.820, p = 0.000). Additionally, behavioral changes mediate the impact of digital technology on community engagement (β = 0.521, p = 0.000), while the preservation of traditional games also contributes to increasing participation (β = 0.164, p = 0.009). These results highlight that while digitalization facilitates traditional games' sustainability, it alters social interactions and generational knowledge transfer. The study suggests that future digital adaptations should balance technological innovations with cultural authenticity to maintain the essence of traditional games. Further research is recommended to explore long-term cultural implications and strategies to effectively integrate digital and traditional gaming practices.